Review of some little-known benthic hydroids (Cnidaria, Hydrozoa) from the Southern Ocean - Cantero, Álvaro L. Peña (Zootaxa, 2015)
A number of benthic hydroid species inhabiting the Southern Ocean are insufficiently characterized. A revision of eight little-known Antarctic species of the order Anthoathecata was made, based on the study of type material. Some of the species have not been recorded since their original description a century ago. Four species (Bimeria corynopsis, Bougainvillia macloviana, ?Koellikerina belgicae and Rhizorhagium antarcticum) belong to the family Bougainvilliidae, two species (Hydractinia angusta and H. dendritica) to the family Hydractiniidae, Perarella clavata to the family Cytaeididae and, finally, Rhysia halecii to the family Rhysiidae. For each species a list of synonyms, a description, a discussion on its relationship with other species and its systematic position, and an account of its autecological data are given. All records found in the literature have been checked.